PELAYANAN ASN MELALUI SUMEDANG SIMPATI ACADEMY (SSA) DI KABUPATEN SUMEDANG - Shofwan Hendryawan; Anisah Yulia Ningsih; Dini Marini; Irmala Regina Wati; Nisa Fauziah; Resti Yuliani (LPPM UNSAP & FISIP UNSAP, 2023)
This study aims to find out, to obtain objective data and information regarding ASN through the Sumedang Simpati Academy (SSA) at the Civil Service Agency and Human Resource Development in Sumedang Regency. The method used in this research is a qualitative research method with a descriptive type. The technique of determining the formal research is purposive sampling. With research informants, namely the Head of the Apparatus Competency Development Sector, the Head Of The Sub-Sector Of Managerial Competency Development, the Head Of The Planning And Evaluation Sub-Sector Of Apparatus Competency Development, the Head Of The Sub-Sector Of Technical And Functional Competency Development, and Staff. Data collection techniques used are library research and field studies which consist of observation, interviews and documentation. While the data processing procedures in this study are data reduction, data display, and data conclusion drawing/verification. The final results of this study conclude that the ASN through the Sumedang Sympathy Academy (SSA) at the Sumedang Regency Personnel and Human Resource Development Agency is already good enough in providing services to the (ASN).